Agrarian reform as tool for sustainable rural development in Valmir Mota settlement in Cascavel, Paraná, Brazil - Zachow, Marlowa; Coutinho, Alan Denizzar Limeira; Grisa, Jaqueline Gomes Demarchi; Barboza, Márcia Andréia; Costa, Patricia Ines; Laskosk, Paulo Alexandre (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2019)
The Landless Movement (MST) emerged as a way to fight for land and land reform, as well as to promote sustainable development. The United Nations (UN), for its part, has been working on 17 goals for sustainable development. Through a case study, we sought to understand how land reform can promote sustainable rural development in the Valmir Mota de Oliveira Settlement, in the city of Cascavel in western Paraná. It was found that the Settlement studied develops various sustainability practices, meeting 8 of the 17 goals of sustainable development proposed by the UN.